"Masking" our emotions: Botulinum toxin, facial expression, and well‐being in the age of COVID‐19. (12th July 2020) - Nestor, Mark S.; Fischer, Daniel; Arnold, David
Abstract: Background: The globally devastating effects of COVID‐19 breach not only the realm of public health, but of psychosocial interaction and communication as well, particularly with the advent of mask‐wearing. Methods: A review of the literature and understanding of facial anatomy and expressions as well as the effect of botulinum toxin on emotions and nonverbal communication. Results: Today, the mask has become a semi‐permanent accessory to the face, blocking our ability to express and perceive each other's facial expressions by dividing it into a visible top half and invisible bottom half. This significantly restricts our ability to accurately interpret emotions based on facial expressions and strengthens our perceptions of negative emotions produced by frowning. The addition of botulinum toxin (BTX)–induced facial muscle paralysis to target the muscles of the top (visible) half of the face, especially the corrugator and procerus muscles, may act as a therapeutic solution by its suppression of glabellar lines and our ability to frown. The treatment of the glabella complex not only has been shown to inhibit the negative emotions of the treated individual but also can reduce the negative emotions in those who come in contact with the treated individual. Conclusions: Mask‐wearing in the wake of COVID‐19 brings new challenges to our ability to communicate and perceive emotion through full facial expression, our most effective and universally shared form of communication, and BTX may offer a positive solution to decrease negative emotions and promote well‐being for both the mask‐wearer and all who come in contact with that individual.